The European Financial and Refugee/Immigrant Crises in the Press: Similarities and Differences of the Greek and German Public Spheres - Stamatis Poulakidakos; Christos Frangonikolopoulos (Global Media Journal: German Edition, 2019)
Having as theoretical basis the notion of the public sphere and its manifestations within the EU, the current paper seeks to trace similarities and differences in the public discourse devel- oped in German and Greek news si tes, regarding the fina ncial and refugee crises. Our quantitative content analysis shows that there are both similari ties and differences in the two distinct public spheres, regarding the evaluation of the EU, its policies on the aforementioned issues and the ways in which the public discourse is being articulated mainly on behalf of politicians and journalists, who appear to be the main carriers of the public discourse in the media under scrutiny.